PERTUMBUHAN DAN HASIL JAGUNG HIBRIDA PULUT PUTIH DENGAN IDEOTIP TANAMAN TEGAK DI KABUPATEN BANJARNEGARA - Nuha, Ulin; Kusuma, Dhoni; Aprilia, Rennanti Lunnadiyah; Rahmawati, Aulia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Corn as a commodity whose use is increasingly widespread today, namely as a direct food ingredient, animal feed and industrial raw material makes this commodity the 2nd commodity whose crop development and expansion has increased sharply in the last 10 years. The aims of this study were: (1) to find out the Pulut hybrids which have better morphological and agronomic characters than the comparison varieties, Pulut URI 1 and URI 2 Pulut varieties. Pulut URI 2 at the Banjarnegara rice field location. This research was conducted using a Randomized Completed Block Design, with 3 replications. If there is a difference in the mean value of the variety in the F test, it is continued with the Least significance different (LSD) test at the 5% significance level. Based on the results of the study, it was concluded that the application of foliar fertilizers did not have a significant effect on the observed variables including plant height, stem diameter, number of leaves, total leaf area, root dry weight and shoot dry weight. Keywords: Corn pulut, Fertilizer, Production